Pengaruh Return on Equity, Komite Audit, dan Debt to Asset Ratio terhadap Nilai Perusahaan : Studi Empiris Perusahaan Sektor Perbankan yang Terdaftar di BEI Tahun 2020-2023 - Rizky Mulasaputra; M. Muhayin A Sidik; Sri Astuti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study investigates the influence of Return on Equity (ROE), the Audit Committee, and the Debt to Asset Ratio (DAR) on firm value in banking companies listed on the Indonesia Stock Exchange for the 2020–2023 period. Firm value is measured using Price to Book Value (PBV). The research is driven by a decline in firm value within the banking sector, which has the potential to affect investor confidence and investment decisions. A quantitative research design is applied, utilizing secondary data derived from published annual financial statements. The research population includes all banking firms listed on the Indonesia Stock Exchange, while the sample is determined through purposive sampling based on specific criteria. Hypothesis testing is conducted using multiple linear regression analysis. The empirical findings indicate that ROE has a significant partial effect on firm value, reflecting the importance of profitability in shaping market perceptions. In contrast, the Audit Committee and DAR do not show a significant individual impact on firm value. However, when examined simultaneously, ROE, the Audit Committee, and DAR collectively influence firm value.